PRODUCTION AND COST OF COLD PATCH ROAD MATS WITH BITUMEN EXTRACTED FROM NIGERIAN TAR SAND (Nigerian Journal of Technology, 2015)
This paper reports the production of bituminous road mats with bitumen sourced from the Nigerian Tar sand, recycled waste rubber and paper, and rock mineral aggregates for cold patching of flexible pavement. The bitumen extracted was evaluated for yield, physical and mechanical properties in accordance with ASTM and AASHTO procedures. The bitumen was mixed with rubber chips to produce rubberized bitumen for production of road mats. The unit cost of production per square metre of the road mat was developed and compared with that of the imported Broom Road Product (BRP). The bitumen extracted from the Nigerian tar sand is suitable as straight run bitumen and production of bituminous cold patch road mats at relatively cheaper cost than the BRP. An immediate action plan for exploitation of the untapped resources of bitumen should be instituted by government and private entrepreneurs for production of road mats for cold patching of flexible roads.   http://dx.doi.org/10.4314/njt.v34i2.5